INDICATION AND OUTCOME OF FORCEPS DELIVERIES IN A TEACHING HOSPITAL - Begum, Iqbal (Journal of Ayub Medical College Abbottabad, 1996)
Of 2811 deliveries between 1st January 1992 to 31st December 1992 in Gynae A Unit, Postgraduate Medical Institute, Lady Reading Hospital, Peshawar, forceps deliveries were 277 (incidence -9.85%). The incidence of failed forceps was 2.16%. The most common group of indications were abnormalities of 2nd stage (53.09%). There were 31 still births and 12 neonatal deaths. The total perinatal deaths were 43. The commonest cause of still birth was birth asphyxia. Most of neonatal deaths were due to prematurity. The perinatal deaths were in cases with preexisting maternal, obstetrical and fetal complications; 60 of our patients had one or other type of complication. The maternal mortality rate was 1.44c /c, forceps not being the cause of these deaths. We have lost 3 patients due to postpartum haemorrhage and one due to eclampsia. The study also showed that maternal morbidity rate was high. Two of our patients had major complications, i.e. uterine rupture and vesicovaginal fistula. The conclusion is that forceps are not free of risk. They are valuable instruments in expert hands. The risks associated with forceps must be balanced against the potentially more serious sequelae associated with caesarean sections.